Gender differentials in poor self-rated health (SRH) among older adults in India: the influence of household air pollution (HAP). - Saha, Jay; Saha, Jayeeta; Roy, Avijit; Chouhan, Pradip (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Background: Although the harmful health effects of ambient air pollution are well known, there is little evidence of the self-reported health effects of household air pollution (HAP). Millions of Indians, especially older women and men, were exposed to high levels of health-damaging air pollutants indoors, adversely affecting their health. Thus, the current study intends to evaluate how diverse HAP factors influence poor self-rated health (SRH) among older adults by gender in India. Data and methods: For this study, 27,090 samples were obtained from wave-1 of the Longitudinal Aging Study in India (LASI). A multivariable binary logistic regression model was used to identify the various contributing factors of poor self-rated health by male and female older adults in India. Results: The adjusted model shows that females who use solid sources of cooking fuel (AOR: 1.37; 95% CI: 1.17 - 1.60) have a higher risk of poor SRH than those who use liquid sources of cooking fuel and those who cook near windows/door (AOR: 1.66; 95% CI: 0.95 - 2.92). Those males who cook near windows/doors and didn't prefer any cooking methods have a higher likelihood of poor SRH. Male respondents who belong to Scheduled Caste (SC), Other Backward Classes (OBC), are Christians, do not go to school, suffer from lung disease, cough, diabetes, and depression have a higher likelihood of poor SRH. Similarly, poor SRH was significantly higher among female older adults who belong to SC, are Christians, have lung disease (AOR: 1.64; 95% CI: 1.19-2.25), cough (AOR: 1.72; 95% CI: 1.41-2.10), diabetes (AOR: 1.90; 95% CI: 1.54-2.34), depression (AOR: 2.07; 95% CI: 1.78-2.42). Conclusion: Exposure to HAP can be reduced by providing cleaner cooking fuels instead of solid cooking fuel and installing upgraded stoves with chimneys and an exhaust fan for residential use. The present study's findings recommend strengthening awareness programs on their consequences for the better health of older adults.